Work-related musculoskeletal disorders among dentists and their prevention through ergonomic interventions - A systematic review (International Journal of Occupational Safety and Health, 2022)
Introduction: Occupational or work-related musculoskeletal disorders (WMSDs) vastly prevail among dental professionals. This review aims to summarize the prevalence of WMSDs and ergonomic interventions for the prevention of WMSDs among dental professionals.Methods: Thorough literature search was done using scientific databases. The terms musculoskeletal disorders among dentists/dental professionals/ hygienists in dentistry, occupational or work-related MSDs, ergonomics, ergonomic interventions, and several combinations were used as keywords. Articles published in the English language only were included. Abstracts, thesis work, and other languages were excluded.Results: Our findings revealed several studies showing the prevalence of WMSD among dental professionals and ergonomic interventions to prevent MSDs among dental professionals.Conclusion: Dental practice is highly challenging both in terms of physical and mental status there is a need for continuing efforts to discover innovative preventive strategies, to reduce the prevalence of WMSDs. This article guides dental professionals to incorporate the proper ergonomic methods in their early stages of day-to-day work, for long-term and healthy dental practice.